Determination of the marginal sash of the caplina river in pachia and calana district by hydraulic modeling - Choque Huanca, Ronald (2020)
In the department of Tacna specifically, the Districts of Pachía and Calana show vulnerability to flooding by maximum avenues, according to the evaluations carried out by the National Water Authority, in the years 2001 and 2019 according to the hydrometric data registry of the Calientes Station, reported flows of 33 m3 / s and 26 m3 / s respectively causing destruction of the intakes of Challata and Calientes, flooding of agricultural areas, leaving the area of the thermal baths in Calientes in flood, clogging of the channeling works of the Caplina river from Calana to the Piedra Blanca sector. The determination of a marginal strip through hydraulic modeling seeks to safeguard the lives of the inhabitants and also the economic and environmental aspects.